Associations between maternal obesity and offspring gut microbiome in the first year of life. Issue 9 (27th April 2022) - Gilley, Stephanie P.; Ruebel, Meghan L.; Sims, Clark; Zhong, Ying; Turner, Donald; Lan, Renny S.; Pack, Lindsay M.; Piccolo, Brian D.; Chintapalli, Sree V.; Abraham, Ann; Bode, Lars; Andres, Aline; et al.
Summary: Background: Maternal obesity is an important determinant of offspring obesity risk, which may be mediated via changes in the infant microbiome. Objectives: We examined infant faecal microbiome, short‐chain fatty acids (SCFA), and maternal human milk oligosaccharides (HMO) in mothers with overweight/obese body mass index (BMI) (OW) compared with normal weight (NW) (Clinicaltrials.gov NCT01131117). Methods: Infant stool samples at 1, 6, and 12 months were analysed by 16S rRNA sequencing. Maternal (BODPOD) and infant (quantitative nuclear magnetic resonance [QMR]) adiposity were measured. HMOs at 2 months postpartum and faecal SCFAs at 1 month were also assessed. Statistical analyses included multivariable and mixed linear models for assessment of microbiome diversity, composition, and associations of taxonomic abundance with metabolic and anthropometric variables. Results: At 1 month, offspring of women with obesity had lower abundance of SCFA‐producing bacteria (including Ruminococcus and Turicibacter ) and lower faecal butyric acid levels. Lachnospiraceae abundance was lower in OW group at 6 months, and infant fat mass was negatively associated with the levels of Sutterella . Gradient boosting machine models indicated that higher α‐diversity and specific microbial taxa at 1 month predicted elevated adiposity at 12 months with overall accuracy of 76.5%. Associations between maternal HMO concentrations and infant bacterial taxa differed between NW and OW groups. Conclusions: Elevated maternal BMI is associated with relative depletion of butyrate‐producing microbes and faecal butyrate in the early infant faecal microbiome. Overall microbial richness may aid in prediction of elevated adiposity in later infancy.